2003
DOI: 10.1289/ehp.111-1241344
|View full text |Cite
|
Sign up to set email alerts
|

Personal PM2.5 exposure and markers of oxidative stress in blood.

Abstract: Ambient particulate air pollution assessed as outdoor concentrations of particulate matter less than or equal to 2.5 micro m in diameter (PM(2.5)) in urban background has been associated with cardiovascular diseases at the population level. However, the significance of individual exposure and the involved mechanisms remain uncertain. We measured personal PM(2.5) and carbon black exposure in 50 students four times in 1 year and analyzed blood samples for markers of protein and lipid oxidation, for red blood cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
100
2
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(116 citation statements)
references
References 36 publications
6
100
2
2
Order By: Relevance
“…Previous studies conducted in adults exposed in occupational 6 settings or to ambient particulate have suggested that malondialdehyde may be a good indicator of the oxidative potential of air pollutants. 25 Higher malondialdehyde levels has been observed in the serum of women exposed to high levels of particulate matter related to burning biomass fuel. 26 Malondialdehyde in the plasma of cement plant workers was negatively correlated with FEV 1 and erythrocyte reduced glutathione.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted in adults exposed in occupational 6 settings or to ambient particulate have suggested that malondialdehyde may be a good indicator of the oxidative potential of air pollutants. 25 Higher malondialdehyde levels has been observed in the serum of women exposed to high levels of particulate matter related to burning biomass fuel. 26 Malondialdehyde in the plasma of cement plant workers was negatively correlated with FEV 1 and erythrocyte reduced glutathione.…”
Section: Discussionmentioning
confidence: 99%
“…This response was found with the particle's organic fraction, and particularly for the particle types that were higher in polyaromatic hydrocarbons, of which PM 2.5 had more than PM 10 . Serensen et al (2003) examined blood markers of oxidative stress in a panel of students and demonstrated an association between elevated plasma oxidative stress and carbon black, a surrogate for elemental carbon. Elevated oxidative stress has also been observed in animal lungs and heart.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding pathway 2, pulmonary oxidative stress may be responsible for instigating the systemic CV pro-oxidative [61][62][63][64][65][66][67][68] and pro-inflammatory [69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] chain reaction observed after PM exposure. Cardiac tissue oxidative stress increases within hours of PM 2.5 inhalation [61], whereas footprints (e.g.…”
Section: Biological Mechanismsmentioning
confidence: 99%